2022
DOI: 10.22437/jbsmr.v5i2.18555
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intellectual Capital on Company Performance and Company Value Before and During Covid-19 Pandemic

Abstract: This study aims to examine the effect of Value added Intellectual capital (VAIC) consist of Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), Capital Employed Efficiency (CEE) on company performance and company value before and during the Covid-19 pandemic. The sample of this research is companies listed on the Indonesia Stock Exchange for the Mining Industry period 2017-2021. The results of this study before covid HCE, SCE and Size had a negative and significant effect on company performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…A culture that promotes innovation, creativity, and knowledge sharing is crucial, as is investing in the latest technology and infrastructure. Collecting and analyzing data can improve decision-making, identify new opportunities, and create new products and services, contributing to the growth of intellectual capital [3] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A culture that promotes innovation, creativity, and knowledge sharing is crucial, as is investing in the latest technology and infrastructure. Collecting and analyzing data can improve decision-making, identify new opportunities, and create new products and services, contributing to the growth of intellectual capital [3] .…”
Section: Resultsmentioning
confidence: 99%
“…The study of Ahmed, et al [2] considered the impact of intellectual capital on the efficiency and value of companies through investing in specific components of intellectual capital and proved the importance of developing an intellectual capital management system. Fitriaty, et al [3] identified intellectual capital as the key to efficient use of resources and a prerequisite for encouraging companies to create additional value.…”
Section: Introductionmentioning
confidence: 99%
“…The higher the quality of financial reporting, the more company information is reflected in financial reports (Sitorus & Murwaningsari, 2019). According to Patricia & Rusmanto, (2022), in Gul et al (2002 conservatism is a careful reaction in the face of uncertainty, where in the face of uncertainty companies consider the inherent risks in the business environment, this is confirmed by Handojo (2012) who states that conservatism causes the reported data to not be interpreted correctly, because what is reported in the financial statements is about figures that range for favorable matters but relatively high numbers for detrimental matters. Brigham and Houston, (2010: 108) state that free cash flow means cash flow that is actually available to be paid to all investors after the company has placed all of its investments in fixed assets, new products, and working capital needed to maintain operations.…”
Section: Introductionmentioning
confidence: 99%
“…International Journal of Economics https://journal.sinergi.or.id/ Firm Value is influenced by several factors(Puspitasari et al, 2023) among others is conservatism accounting Patricia & Rusmanto, (2022). explains accounting conservatism is principle caution in recording and presentation report finance , that is , in order for the company No quick confess assets and profits , however quick Possible confess possible losses and debts will happened .…”
mentioning
confidence: 99%